Promising Immunomodulatory Effects of Bacterial Lysates in Allergic Diseases - Kaczynska, Agnieszka; Klosinska, Martyna; Janeczek, Kamil; Zarobkiewicz, Michał; Emeryk, Andrzej (Frontiers in Immunology, 2022)
In light of an escalating prevalence of allergic disorders, it is crucial to fully comprehend their pathophysiology and etiology. Such knowledge would play a pivotal role in the search for new therapeutic approaches concerning not only diseases’ symptoms, but also their underlying causes. The hygiene hypothesis indicates a high correlation between limited exposure to pathogens in early childhood and the risk of developing allergic disorders. Bearing in mind the significance of respiratory and digestive systems’ mucous membrane’s first-line exposure to pathogens as well as its implications on the host’s immune response, a therapy targeted at aforesaid membranes could guarantee promising and extensive treatment outcomes. Recent years yielded valuable information about bacterial lysates (BLs) known for having immunomodulatory properties. They consist of antigen mixtures obtained through lysis of bacteria which are the most common etiologic agents of respiratory tract infections. They interact with dendritic cells located in the mucous membranes of the upper respiratory tract and the gastrointestinal tract by toll-like receptors. The dendritic cells present acquired antigens resulting in innate immune response development on the release of chemokines, both stimulating monocytes and NK cells maturation and promoting polymorphonuclear neutrophil migration. Moreover, they influence the adaptive immune system by stimulating an increase of specific antibodies against administered bacterial antigens. The significance of BLs includes not only an anti-inflammatory effect on local infections but also restoration of Th1/Th2 balance, as demonstrated mainly in animal models. They decrease Th2-related cytokine levels (IL-4, IL-13) and increase Th1-related cytokine levels (IFN-γ). The reestablishment of the balance of the immune response leads to lowering atopic reactions incidence which, in addition to reduced risk of inflammation, provides the alleviation and improvement of clinical manifestations of allergic disorders. In this review, we hereby describe mechanisms of BLs action, considering their significant immunomodulatory role in innate immunity. The correlation between local, innate, and adaptive immune responses and their impact on the clinical course of allergic disorders are discussed as well. To conclude our review, we present up-to-date literature regarding the outcomes of BLs implemented in atopic dermatitis, allergic rhinitis, and asthma prevention and treatment, especially in children.